Hypoxia Inducible Factor Pathway and Physiological Adaptation: A Cell Survival Pathway? - Hemant Kumar; Dong-Kug Choi (Mediators of Inflammation)
Oxygen homeostasis reflects the constant body requirement to generate energy. Hypoxia (0.1–1% O2), physioxia or physoxia (∼1–13%), and normoxia (∼20%) are terms used to define oxygen concentration in the cellular environment. A decrease in oxygen (hypoxia) or excess oxygen (hyperoxia) could be deleterious for cellular adaptation and survival. Hypoxia can occur under both physiological (e.g., exercise, embryonic development, underwater diving, or high altitude) and pathological conditions (e.g., inflammation, solid tumor formation, lung disease, or myocardial infarction). Hypoxia plays a key role in the pathophysiology of heart disease, cancers, stroke, and other causes of mortality. Hypoxia inducible factor(s) (HIFs) are key oxygen sensors that mediate the ability of the cell to cope with decreased oxygen tension. These transcription factors regulate cellular adaptation to hypoxia and protect cells by responding acutely and inducing production of endogenous metabolites and proteins to promptly regulate metabolic pathways. Here, we review the role of the HIF pathway as a metabolic adaptation pathway and how this pathway plays a role in cell survival. We emphasize the roles of the HIF pathway in physiological adaptation, cell death, pH regulation, and adaptation during exercise.